Konsep Tauhid dalam Naskah Sifat Dua Puluh Koleksi British Library - Haning Intan Prastiwi; Asep Yudha Wirajaya (Balai Bahasa Provinsi Riau, 2022)
The Attribute of Twenty is an obligatory attribute of Allah that Muslims need to know to further strengthen their belief in the Creator. The manuscript that will be used in this research is the Nature Twenty manuscript numbered M.S. 13716 stored in the British Library. The Text of the Twenty Traits contains the obligatory attributes of Allah. The description of the attributes of Allah is also accompanied by the arguments of the Qur'an, followed by an explanation of the meaning of these attributes. By using a philological approach, this research aims to reveal the problem of His monotheism. The concept of monotheism contained in the text of the Twenty Traits, among others, shows that Allah is the One who creates life and death, belonging to Him is the dominion of the heavens and the earth, Allah is only one and no one can associate partners with Him, and His servants are obliged to believe in all of Allah's attributes as a provision. in the afterlife. These concepts are described in the twenty attributes of Allah that are contained in the text of the Attribute of Twenty.